2004
DOI: 10.1074/jbc.m401157200
|View full text |Cite
|
Sign up to set email alerts
|

Specific Residues in Plasmatocyte-spreading Peptide Are Required for Receptor Binding and Functional Antagonism of Insect Immune Cells

Abstract: Plasmatocyte-spreading peptide (PSP) is a 23-amino acid cytokine that activates a class of insect immune cells called plasmatocytes. PSP consists of two regions:an unstructured N terminus (1-6) and a highly structured core (7-23). Prior studies identified specific residues in both the structured and unstructured regions required for biological activity. Most important for function were Arg 13 , Phe 3 , Cys 7 , Cys 19 , and the N-terminal amine of Glu 1 . Here we have built on these results by conducting cell b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
(49 reference statements)
0
20
0
Order By: Relevance
“…Rather than independently mediating hemocyte spreading, we propose a model (Fig. 8), in which PSP interacts with a hemocyte surface receptor, most likely the 190-kDa protein reported earlier (Clark et al, 2004). In our model, receptor binding activates PLA 2 , which migrates to a membranous cell fraction, where it Figure 8.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Rather than independently mediating hemocyte spreading, we propose a model (Fig. 8), in which PSP interacts with a hemocyte surface receptor, most likely the 190-kDa protein reported earlier (Clark et al, 2004). In our model, receptor binding activates PLA 2 , which migrates to a membranous cell fraction, where it Figure 8.…”
Section: Discussionmentioning
confidence: 94%
“…The proPSP is activated by a proteolytic cleavage to a 23 residue PSP that mediates plasmatocyte spreading (PS) (Clark et al, 1998). This is the first reported insect cytokine and it acts via an approximately 190-kDa receptor to induce PS (Clark et al, 2004). The P. includens PSP also mediates hemocyte spreading and aggregation behaviors of other lepidopteran species, including Spodoptera exigua, in a dose-dependent manner Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmatocytes are normally non-adhesive and must be activated by cytokines in hemolymph in order to bind and spread onto foreign surfaces. The most potent known activator of plasmatocytes is the plasmatocyte-spreading peptide (PSP) (Clark et al, 1997), homologs of which have been identified from a number of other moth species, including M. sexta (Clark et al, 2004). PSP and related homologs are the only molecules identified to date that activate plasmatocytes (Clark et al, 1997;Strand et al, 2000;Miura et al, 2002;Nakahara et al, 2003), although circumstantial evidence suggests that several other molecules besides PSP mediate plasmatocyte function (Lackie, 1988;Gillespie et al, 1997;Lavine and Strand, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Hemocytes were collected from non-parasitized fifth instars by anesthetizing larvae with CO 2 and bleeding them from an incision across the last abdominal segment. Hemolymph was collected in a microfuge tube containing anticoagulant buffer (98 mM NaOH, 186 mM NaCl, 17 mM Na 2 EDTA, and 41 mM citric acid, pH adjusted to 4.5) (Clark et al, 2004). spherule cells plus oenocytoids were isolated on Percoll gradients as previously described (Pech and Strand, 1996 (Gardiner and Strand, 1999 (Strand et al, 1992;Strand, 1994 (Strand, 1994;Trudeau et al, 2000;Beck and Strand, 2003).…”
Section: Introductionmentioning
confidence: 99%